Experimental Evaluation of Adaptive Modulation and Coding in MIMO WiMAX with Limited Feedback. (11th May 2008) - Mehlführer Mehlführer, Christian Christian; Caban Caban, Sebastian Sebastian; Rupp Rupp, Markus Markus
Abstract : We evaluate the throughput performance of an OFDM WiMAX (IEEE 802.16-2004, Section 8.3) transmission system with adaptive modulation and coding (AMC) by outdoor measurements. The standard compliant AMC utilizes a 3-bit feedback for SISO and Alamouti coded MIMO transmissions. By applying a 6-bit feedback and spatial multiplexing with individual AMC on the two transmit antennas, the data throughput can be increased significantly for large SNR values. Our measurements show that at small SNR values, a single antenna transmission often outperforms an Alamouti transmission. We found that this effect is caused by the asymmetric behavior of the wireless channel and by poor channel knowledge in the two-transmit-antenna case. Our performance evaluation is based on a measurement campaign employing the Vienna MIMO testbed. The measurement scenarios include typical outdoor-to-indoor NLOS, outdoor-to-outdoor NLOS, as well as outdoor-to-indoor LOS connections. We found that in all these scenarios, the measured throughput is far from its achievable maximum; the loss is mainly caused by a too simple convolutional coding.